2020
DOI: 10.5194/gchron-2020-27
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

U–Pb geochronology of epidote by LA–ICP–MS as a tool for dating hydrothermal-vein formation

Abstract: Abstract. Monoclinic epidote is a low-µ (µ = 283U / 204Pb) mineral occurring in a variety of geological environments, participating in many metamorphic reactions and stable throughout a wide range of pressure–temperature conditions. Despite containing fair amounts of U, its use as a U–Pb geochronometer has been hindered by the commonly high contents of initial Pb with isotopic compositions that cannot be assumed a priori. We present U–Pb geochronology of hydrothermal-vein epidote spanning a wide range of Pb (3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In recent years, in situ U-Pb geochronology has been successfully applied to a growing number of mineral matrices, including calcite and dolomite (Burisch et al, 2017), hematite (Walter et al, 2018), opal (Nuriel et al, 2019), cassiterite (Moscati and Neymark, 2020), Mn-rich chrysocolla and pseudomalachite (Kahou et al, 2020), epidote (Peverelli et al, 2020), nacrite and fluorite (Piccione et al, 2019). Piccione et al, (2019) reported for the first time LA-ICP-MS U-Pb ages acquired on fluorite that are consistent with those of adjacent nacrite crystals, showing that fluorite U-Pb geochronology can constrain the timing of fluid flows, providing favorable U/Pb.…”
mentioning
confidence: 99%
“…In recent years, in situ U-Pb geochronology has been successfully applied to a growing number of mineral matrices, including calcite and dolomite (Burisch et al, 2017), hematite (Walter et al, 2018), opal (Nuriel et al, 2019), cassiterite (Moscati and Neymark, 2020), Mn-rich chrysocolla and pseudomalachite (Kahou et al, 2020), epidote (Peverelli et al, 2020), nacrite and fluorite (Piccione et al, 2019). Piccione et al, (2019) reported for the first time LA-ICP-MS U-Pb ages acquired on fluorite that are consistent with those of adjacent nacrite crystals, showing that fluorite U-Pb geochronology can constrain the timing of fluid flows, providing favorable U/Pb.…”
mentioning
confidence: 99%